Experimental studies on use of toggle brace mechanism fitted with magnetorheological dampers for seismic performance enhancement of three‐storey steel moment‐resisting frame model1. Issue 3 (11th October 2011) - Rama Raju, K.; Meher Prasad, A.; Muthumani, K.; Gopalakrishnan, N.; Iyer, Nagesh R.; Lakshmanan, N.
SUMMARY The supplemental passive and semi‐active dampers such as viscous fluid dampers and magnetorheological (MR) dampers normally placed in either Chevron or Toggle brace are increasingly used to provide enhanced seismic protection for new/retrofit existing buildings and bridges. The experimental nonlinear force–velocity relationships of MR dampers at different current inputs are fitted to fractional velocity power law. A three‐storey quarter length scale steel moment‐resisting frame model with two MR dampers fixed in upper toggle brace mechanism placed at ground floor level is designed and fabricated to study its seismic response characteristics. The natural frequencies and corresponding damping ratios of the model with MR damper at different current inputs are found. A procedure for modeling of MR dampers as nonlinear viscous fluid dampers is described. A methodology to find effective damping of the structural model is developed, using the formulations for nonlinear viscous fluid dampers given in literature. The methodology developed is used for finding the effective damping of structural model fitted with MR dampers in upper toggle bracing mechanism in different storeys of frame model. The model is subjected to two types of seismic excitations, and from studies of responses, it is found that the reduction in responses because of provision of MR dampers are to be quite significant. Copyright © 2011 John Wiley & Sons, Ltd.